Epidemiological characteristic of cardiovascular risk factors and diet patterns in schoolchildren - L. V. El’garova; A. A. El’garov; A. M. Kardangusheva (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To assess epidemiological situation regarding cardiovascular disease (CVD) risk factors (RF) and diet patterns in schoolchildren. Material and methods. A representative sample, selected from organized population of Kabardino-Balkaria Republic schoolchildren, was examined by epidemiology methods. Survey with a standard questionnaire, anthropometry, tonometry, total cholesterol, high-density lipoprotein cholesterol levels measurement, daily diet survey, and mailing survey of parents were performed. RF prevalence was estimated by standard criteria. Results were analyzed according to age, gender, nationality, region and type of location. Results. Prevalence of main CVD RF was calculated. Age-, gender-, climate-geographic, and national-specific patterns of low physical activity, dyslipidemia, high blood pressure, overweight, and smoking were examined. Data on actual diet of schoolchildren, and its link to RF levels were obtained. Correlation between CVD RF prevalence in children and adolescents, from one hand, and professional and educational status of their parents, from another hand, was studied. Conclusion. High RF prevalence in schoolchildren points to poor epidemiology situation with CVD risk, as well as to a need for multi-factor population-level preventive programs.